A survey of traditional Chinese medicine consumers to investigate the impact of China's legalization of rhino horn trade on stigmatization and likelihood of use. Issue 11 (21st September 2021) - Cheung, Hubert; Mazerolle, Lorraine; Possingham, Hugh P.; Biggs, Duan
Abstract: Rhino poaching continues to threaten species survival despite decades‐long trade bans, with rhino horn use in traditional Chinese medicine (TCM) contributing to global demand. Conservationists have debated over policy alternatives like trade legalization, and insight into TCM stakeholders is needed to support policymaking. The need for more research became made more urgent with China's 2018 decision to initiate the process of legalizing domestic trade. In this study, we conducted a large‐scale online survey of TCM consumers in Guangdong province, China. We found that while stigmatization of rhino horn use is limited at present, it is likely to drop further with trade legalization. Prescription usage will be the most likely source of increased rhino horn demand if trade is legalized. Given the terms established in China's 2018 policy document, we stress the importance of engaging constructively with policymakers and TCM stakeholders to influence the process of establishing medical standards and regulatory mechanisms such that clinical access in a future legal trade is stringently controlled. Abstract : China's intention to legalize the domestic trade in rhino horn has raised serious conservation concerns. Here, we conducted a large scale survey of TCM consumers in China to investigate how trade legalization could impact stigmatization and likelihood of use.